Effect of aging on magnetic resonance measures differentiating progressive supranuclear palsy from Parkinson's disease. Issue 4 (26th February 2014) - Morelli, Maurizio; Arabia, Gennarina; Messina, Demetrio; Vescio, Basilio; Salsone, Maria; Chiriaco, Carmelina; Perrotta, Paolo; Rocca, Federico; Cascini, Giuseppe Lucio; Barbagallo, Gaetano; Nigro, Salvatore; Quattrone, Aldo
ABSTRACT Imaging measurements, such as the ratio of the midsagittal areas of the midbrain and pons (midbrain/pons) and the Magnetic Resonance Parkinsonism Index (MRPI), have been proposed to differentiate progressive supranuclear palsy (PSP) from Parkinson's disease (PD). However, abnormal midbrain/pons values suggestive of PSP have also been reported in elderly individuals and in patients with PD. We investigated the effect of aging on single or combined imaging measurements of the brainstem. We calculated the midbrain/pons and the MRPI (the ratio of the midsagittal areas of the pons and the midbrain multiplied by the ratio of the middle cerebellar peduncle and superior cerebellar peduncle widths) in 152 patients affected by PD, 25 patients with PSP, and a group of 81 age‐matched and sex‐matched healthy controls using a 3‐Tesla magnetic resonance imaging scanner. In healthy controls, aging was negatively correlated with midsagittal area of the midbrain and midbrain/pons values. In patients with PD, in addition to the effect of aging, the disease status further influenced the midbrain/pons values (R2 = 0.23; P < 0.001). In both groups, MRPI values were not influenced either by aging or by disease status. No effect of aging on either midbrain/pons or MRPI values was shown in the patients with PSP. Our findings indicated that the MRPI was not significantly influenced by aging or disease‐related changes occurring in PD; whereas, in contrast, the midbrain/pons was influenced. Therefore, the MRPI appears to be a more reliable imaging measurement compared with midbrain/pons values for differentiating PSP from PD and controls in an elderly population. © 2014 International Parkinson and Movement Disorder Society